Effect of Courtyard Position in Creating Indoor Thermal Comfort - Silfia Mona Aryani; Ari Diana Susanti; Soepono Sasongko (Tesa Arsitektur, 2019)
The courtyard existance that has been recommended in some publication may need to be promoted and hence prioritized on every Rumah sederhana Sehat (RsS) development. In order to support the courtyard promotion initiative, evidence based on research into RsS courtyards’ characteristic that inform the maintenance of optimal indoor thermal comfort, needs to be acquired. This paper examines the issue of the RsS courtyard’s position as one of the factors that is effective in both establishing and maintaining each house’s indoor thermal comfort. The research is conducted with Ansys 14.5 Fluid CFD simulation. The unit model itself is a 9 x 9 m2 unit house. A 3 x 3 m2 courtyard, in 9 different placements, is tested for its effectiveness in maintaining the RsS model’s indoor thermal comfort. Based on the results and the discussion, it can be concluded that there are 5 courtyard positions that provide the RsS houses and their residents with comfortable indoor temperatures. Therefore, these five positional options can be proposed as viable courtyard placements, especially the two positions that show superior performance to the other three acceptable courtyard locations.